Stories of addiction recovery the G-CHIME model - Ogilvie, Lisa; Carson, Jerome (Emerald Publishing, 2023)
Stories of Addiction Recovery explores first-hand structured accounts of addiction recovery through the G-CHIME model. G-CHIME is an adaptation to the CHIME model of mental health recovery, specifically targeted at addiction recovery. Identifying important components of recovery (Growth, Connectedness, Hope, Identity, Meaning in life, and Empowerment), G-CHIME considers aspects of positive psychology such as empowerment and hope as well as recognizing elements of addiction recovery such as connection and meaning in life. Publishing recovery stories in this way Stories of Addiction Recovery contributes positive literature to an area that is conventionally viewed with a negative bias, building away from the long-standing stigmatization associated with addiction and substance misuse. The first-hand accounts of shared experiences, lessons learnt, and the growth achieved can highlight to others what is possible in their own recovery.
Includes bibliographical references and index
Keywords: Substance abuse / Treatment; Addicts / Rehabilitation; Medical; Mental Health; Drug & substance abuse: social aspects